Fiscal Policy in Poland in the Times of Crisis - Origins and Consequences - Krajewski, Stefan; Krajewska, Anna (Comparative Economic Research. Central and Eastern Europe, 2011)
The present crisis has forced almost all countries to introduce an active economic policy. A lot of attention has been paid to fiscal policy and taxes in Poland. The measures taken in Poland differ considerably from global standards and decisions concerning taxes have been generally political in nature. The paper presents solutions in fiscal policy applied in Poland and explains the specificity of Poland's economy and its anti-crisis policy.